Utilização e destino do carbono orgânico dissolvido em um reservatório eutrófico (Barra Bonita, SP) - Panhota, Rafael Spadaccia (2007)
The stocks of dissolved organic compounds from the aquatic environments represent one of the largest bulks of active organic C in the biosphere. It is thoroughly accepted that the dissolved organic matter represents a dynamic component in the interaction among geosphere, hydrosphere and biosphere and as such, has potential to influence the global carbon cycle. Perhaps the most important characteristic of the dissolved organic matter is its bioavailability potential. Due the complex mixture of organic compounds, ultrafiltration techniques have been used to fractionate DOM in compounds of different molecular weights seeking for better understanding of dynamic and bacterioplankton uptakes. In this context, this study aim to quantify the seasonal variation of dissolved organic carbon concentrations; the proportion of high and low molecular weight compounds and also to verify such variations in function of some limnological variables of an eutrophic tropical reservoir (Barra Bonita, SP). Also, through bioassays, to determine the loss mass coefficients and the degradation routes of different resources (DOC presents in reservoir s water and Pistia stratiotes and Eichhornia crassipes leachates) and their high (> 10 kDa) and low (< 10 kDa) molecular weight fractions. The results showed that DOC concentrations were higher in the rainy season, probability due the increase in primary production (stimulated by the largest concentration of nutrients, mainly phosphorus) and allochthonous material input, with predominance of compounds of high molecular weight. In the bioassays, the leaching of aquatic macrophytes presented higher loss mass coefficients than DOC in the reservoir s water, which the main mineralization route was the fast oxidation biological/chemistry (labile fraction). The POC formation generated low yield, being P. stratiotes leacheate higher POC producer than E. crassipes. The leachates with low molecular weight compounds were more uptaken than high molecular weight and they generated higher oxygen demand. In the decomposition experiment of reservoir s DOC, the slow oxidation biological/chemistry (refractory fractions) was the main mineralization route, the POC formation presented low yield and the oxygen demand was smaller in relation to the leachates. The results indicated possible variations in the use and fate of DOC for the bacterioplankton of different areas of the reservoir.